CFD analysis of a rotary kiln using for plaster production and discussion of the effects of flue gas recirculation application - Guertuerk, Mert; Öztop, Hakan Fehmi; Pambudi, Nugroho Agung (Springer, 2018)
In this study, the CFD analysis of the rotary kiln is carried out for examining effects of various parameters on energy consumption and efficiency of the rotary kiln. The flue gas recirculation using in many applications is a useful method for combusting of fuel unburned in the flue gas. Also, effects of flue gas recirculation on the combusting of fuel, operating temperature and efficiency of the rotary kiln are discussed in this study. The rotary kiln, which is considered in this study, is used in plaster plant. Two different CFD models were created and these models are compared according to many parameters such as temperature distribution, mixture fraction, the mass fraction of O-2, CO, CO and CH4 in the combustion chamber. It is found that the plaster plant has a great potential for an increase in energy efficiency. Results obtained for producers of rotary kiln and burner will be useful for determining better design parameters.
Keywords: Mass-Transfer; Combustion